Writing Machine Using Voice Command (International Journal of Scientific Research in Science and Technology, 2026)
The Writing Machine Using Voice Command is an automated assistive system designed to convert human speech into handwritten text on paper. The proposed system integrates voice recognition, Bluetooth-based wireless communication, embedded control, and robotic motion to enable hands-free writing. Voice commands provided through a smartphone or voice-enabled device are converted into text and transmitted to an Arduino-based microcontroller (ATmega328P), which interprets the input and generates motion commands for the writing mechanism. Stepper motors driven by an A4988 motor driver enable precise movement along the horizontal and vertical axes, while a servo motor controls the pen’s up and down motion. Mechanical components such as smooth rods, lead screws, POM wheels, pulleys, and timing belts ensure stability and accurate handwriting reproduction. Experimental results demonstrate reliable wireless communication, smooth motor operation, and consistent handwritten output. The proposed system reduces the need for manual writing and provides a low-cost, portable, and effective assistive solution for physically challenged individuals, educational applications, and automation of repetitive writing tasks.